Teks-teks Lakon Wayang Karya Ki Widiprayitna Eks-Koleksi J. L. Moens: Jembatan Masa Lalu terhadap Kajian Filologi Pertunjukan - Bima Slamet Raharja (Manuskripta, 2026)
This article examines the continuity and evolution of lakon wayang texts within the J.L. Moens collection, specifically those rewritten by Ki Widiprayitna. Moens’ initiative was pivotal in documenting Yogyakarta’s puppetry traditions, drawing from ancestral guidelines like Pancakaki and Grenteng. Widiprayitna’s adaptations mirror live performances, meticulously preserving structural elements such as janturan (narrative descriptions), pocapan (dialogue), and gendhing (musical cues). These texts, including the Pakem Ringgit Purwa, serve as vital records of the transition from oral performance to written media. The inclusion of character illustrations further enhances the dramatic technicality of these records. By applying philological transcription to Widiprayitna’s work, researchers can decode the essential symbols and modes that define these standardized plays. Ultimately, this study highlights Widiprayitna’s critical role in formalizing and preserving the rich heritage of Javanese shadow puppetry for future generations. === Artikel ini membahas eksistensi, kesinambungan, dan transformasi teks lakon wayang dalam koleksi J.L. Moens yang ditulis ulang oleh Ki Widiprayitna. Upaya Moens merupakan langkah krusial dalam mendokumentasikan pengetahuan pedalangan di Yogyakarta berdasarkan pakem-pakem leluhur seperti Pancakaki dan Grenteng. Tulisan yang dihimpun Widiprayitna disusun identik dengan struktur pertunjukan asli, mencakup elemen janturan, pocapan, hingga gendhing. Proses ini menandai peralihan medium dari pertunjukan lisan ke bentuk tertulis. Teks seperti Pakem Ringgit Purwa dalam koleksi ini menyimpan detail teknis serta rekaman sejarah pertunjukan masa lalu. Kehadiran ilustrasi tokoh wayang turut memperjelas aspek dramatik dan karakterisasi dalam cerita. Melalui transkripsi filologis terhadap karya Widiprayitna, kode, mode, dan simbol penting dapat terungkap. Secara keseluruhan, studi ini menyoroti peran vital Widiprayitna sebagai produser teks standar dalam melestarikan warisan budaya wayang kulit bagi generasi mendatang.